The novel dipeptide Tyr-Ala (TA) significantly enhances the lifespan and healthspan of Caenorhabditis elegans. Issue 4 (17th March 2016) - Zhang, Z.; Zhao, Y.; Wang, X.; Lin, R.; Zhang, Y.; Ma, H.; Guo, Y.; Xu, L.; Zhao, B.
Abstract : Food-derived bioactive peptides may have various physiological modulatory and regulatory functions and are now being studied extensively. Abstract : Food-derived bioactive peptides may have various physiological modulatory and regulatory functions and are now being studied extensively. Recently, the novel dipeptide Tyr-Ala was isolated from hydrolyzed maize protein. Tyr-Ala significantly prolonged the lifespan of wild-type Caenorhabditis elegans and extended the nematode healthspan and lifespan during heat/oxidative stress. Compared with its constituent amino acids, Tyr-Ala was more efficient in enhancing stress resistance. Further studies demonstrated that the significant longevity-extending effects of Tyr-Ala on Caenorhabditis elegans were attributed to its in vitro and in vivo free radical-scavenging effects, in addition to its ability to up-regulate stress resistance-related proteins, such as SOD (Superoxide Dismutase)-3 and HSP (Heat Shock Protein)-16.2. Real-time PCR results showed that the up-regulation of aging-associated genes, such as daf-16, sod-3, hsp-16.2 and skn-1, also contributed to the stress-resistance effect of Tyr-Ala. These results indicate that the novel dipeptide Tyr-Ala can protect against external stress and thus extend the lifespan and healthspan of Caenorhabditis elegans . Thereby, Tyr-Ala could be used as a potential medicine in anti-aging research.